Investigation on diffusion bonding characteristics of aluminum metal matrix composites (Al/SiCp) with pure aluminum for different heat treatments - Muratoglu, M.; Yilmaz, O.; Aksoy, A. (Elsevier Science Sa, 2006)
Joining characteristic of SiC particulate reinforced aluminum metal matrix composites (MMCs) with pure aluminum were investigated by diffusion bonding process. The joining quality of the Al/SiCp MMCs was studied to determine the influences of SiCp particulates with homogenization and age hardening on bonding properties. The experimental results indicate that the application of aging before and after diffusion bonding decreases SiC particulate accumulation, and increases other elemental concentration at interface. Especially, the application of aging treatment before the diffusion bonding of Al/SiCp MMCs to pure Al, increased Cu% concentration at interface which treats as the insert alloy. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: diffusion bonding; metal matrix composites; heat treatments